Partitoning of phosphate fertilizaton at planting and cover of tomato - Mueller, Siegfried (2018)
Abstract – The objective of this work was to evaluate the eﬀect of the phosphate fertilizer applied in the planting and in the sidedressing on the yield of ‘Alambra’ tomato. The experiments were carried out in the field at Epagri, Experimental Station of Caçador-SC, in the 2011/12 and 2012/13 harvests period. The experimental design was a randomized block design, with five replications. The treatments were composed of six percentages of P2O5 applied to planting and covering, respectively, in relation to the total dose of this nutrient (800 kg ha-1): 0 and 100; 20 and 80; 40 and 60; 60 and 40; 80 and 20; 100 and 0%. As P sources, triple superphosphate was used for planting applications and purified monoammonium phosphate for fertigation applications. The P in fertigation was applied in the amount corresponding to the percentage predicted for each treatment, viafertigation, in eight applications from 21 days to 77 days after planting. There is an increase in ‘total’, ‘marketable’ and ‘extra AA’ yields of tomato fruits as the percentage of P incorporated in the planting is increased, compared to the application in sidedressing via fertirrigation, with the highest productivity obtained with 100 % of P applied at planting.